2016
DOI: 10.1111/jan.13157
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a home‐based training programme to decrease depression in family caregivers of persons with dementia

Abstract: NCT02667951.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
(135 reference statements)
1
23
0
Order By: Relevance
“…In SGH, we have a structured caregiver-training programme to equip our caregivers with knowledge and skills so that they can pro- more likely to experience positive outcomes compared to caregivers who did not attend (Hendrix et al, 2016;Kuo et al, 2017). In this study, we found no beneficial effect of caregiver training.…”
Section: Factors Associated With the Four Types Of Caregiver Reactionsmentioning
confidence: 53%
See 1 more Smart Citation
“…In SGH, we have a structured caregiver-training programme to equip our caregivers with knowledge and skills so that they can pro- more likely to experience positive outcomes compared to caregivers who did not attend (Hendrix et al, 2016;Kuo et al, 2017). In this study, we found no beneficial effect of caregiver training.…”
Section: Factors Associated With the Four Types Of Caregiver Reactionsmentioning
confidence: 53%
“…Such a training programme is beneficial, especially for caregivers who need to provide specialised caregiving tasks such as changing catheter bags, wound care or overseeing complex medication management. Studies have shown that caregivers who attended a caregiver‐training programme were more likely to experience positive outcomes compared to caregivers who did not attend (Hendrix et al, ; Kuo et al, ). In this study, we found no beneficial effect of caregiver training.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the reductions in depression and anxiety were most significant in those caregivers who presented higher level prior to the intervention (Hatch et al, ). An increase in depressive symptomatology was observed in the CG postintervention (Gitlin et al, ; Kuo et al, ) and caregiver burden was associated with provision of constant care due to deterioration in the functional capacities of the PwD, resulting in dedication of more time to caregiving activities (Kuo et al, ; Kwok et al, ). Similarly, it was observed that the level of burden depended on the presence or otherwise of externally recruited caregivers (Hatch et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the studies analysed and classified into this category, (N= 7), three divided the sessions into home sessions, where the caregivers could access a programme from their own homes though a web portal and telephone sessions with a health professional who was part of the educational programme (Beauchamp, Irvine, Seeley, & Johnson, 2005;Hattink et al, 2015;Kajiyama et al, 2013). Four studies, delivered the programme through telephone networks, that is, a health professional explained the sessions to the caregiver by phone, so that queries were dealt with immediately (Gitlin et al, 2010;Hatch et al, 2013;Kuo et al, 2016;Kwok et al, 2013;Tremont, Davis, Bishop, & Fortinsky, 2008). In the three remaining studies, the programme included a web page, divided into specific sessions for the home care of the PwD.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation